A new species of Vriesea (Bromeliaceae) from Pedra dos Pontões, Espírito Santo, Brazil: an area of endemism for Bromeliaceae at Atlantic Forest - Couto, Dayvid R.; Kessous, Igor M.; Costa, Andrea F. (Phytotaxa, 2020)
Vriesea mimosoensis is described and illustrated as a new taxon from the Atlantic Forest in Espírito Santo, Southeastern Brazil. Morphological comparisons of this taxon with related species are presented. Here we discuss taxonomy comments, etymology, geographical distribution and the conservation status of this new species.